Prevalence and factors associated with incomplete immunization of children (12-23 months) in Kwabre East District, Ashanti Region, Ghana - Anthony Wemakor; Gideon Kofi Helegbe; Alhassan Abdul-Mumin; Shadrack Amedoe; Jessica Adjoa Zoku; Ahimah Ivy Dufie (BMC, 2018)
Abstract Background Childhood immunization is one of the most cost effective health interventions but its rate has been declining recently in Ghana. Information on immunization coverage and determinants is needed to improve immunization programmes. The objective of this study was to determine the prevalence and factors associated with incomplete immunization of children (12-23 months) in Kwabre East District, Ghana. Methods A cross-sectional, community-based survey involving 322 children and their mothers was carried out. Data were collected on socio-demographic characteristics of mothers, childhood immunization history and mothers' knowledge and practices of immunization using a structured questionnaire. Children were classified as incompletely immunized if they failed to receive at least one of 8 vaccine doses: - one dose of Bacillus Calmette-Guérin (BCG), 3 doses each of pentavalent, 3 doses of polio and one dose of measles per WHO/UNICEF definition. Chi-square and logistic regression analyses were used to identify the factors associated with incomplete immunisation. Results The prevalence of incomplete immunization was low (15.5%) suggesting high immunisation coverage but the coverage of the second measles dose, taken at 18 months of age, was the lowest (23.9%). Most of the mothers knew the importance of immunisation (95.7%) and at least one vaccine-preventable disease or symptom (84.9%). Two factors associated with incomplete immunisation in bivariate analyses (community of residence, and mother's knowledge of number of oral polio vaccines given to children) were no longer significant in a logistic regression model. Compared to children in Aboaso, children in Gyamfi Wonoo (AOR = 1.81, 95% CI = 0.80-4.08), Mamponteng (Bonwunu) (AOR = 0.59, 95% CI = 0.24-1.48) and Mamponteng (Town) (AOR = 0.63, 95% CI = 0.26-1.55) had similar odds of incomplete immunisation. Similarly, mother's lack of knowledge of the number of doses of polio vaccine given to children had no effect on the odds of incomplete immunisation (AOR = 0.53, 95% CI = 0.22-1.26). Conclusions Immunization coverage is high in the Kwabre East district but very few children received the second measles dose. None of the maternal and child factors assessed is associated with immunisation coverage. Further research is needed to identify the determinants of immunisation coverage and the reasons for the low uptake of second measles dose in the study area.